Fármacos para tratamento da COVID-19 - Marto, Natalia (2020)
The novel severe acute respiratory syndrome coronavirus 2 is the cause of Coronavirus Disease 2019, a new illness with no effective treatment or vaccine that has reached pandemic proportions. In this document, we analyze how health authorities and agencies around the world position themselves regarding the off-label use of repurposed drugs or new investigational drugs to treat Coronavirus Disease 2019. We review the most promising candidate medicines, including available evidence, clinical recommendations and current options for access. Our concluding remarks stress the importance of administering off-label and investigational drugs in the setting of clinical trials, or at least in standardized scenarios, to generate as much scientific knowledge as achievable while engaging in the best efforts to treat patients and save lives.